PENJADWALAN ULANG PRODUKSI FUSELAGE DAN TAIL UNIT PADA PESAWAT TIPE CN235 MENGGUNAKAN SKENARIO WAKTU KERJA - Fathul Islam, Muhammad
PT Dirgantara Indonesia (PT DI) is one of the State-Owned Enterprises (SOEs) engaged in the aeronautical industry. PT DI has several types of products ranging from aircraft to civilian, military, helicopter, and others. In addition to distributing finished units, PT DI also accepts orders in the form of subassembly components as per client's request. One of the existing orders is the request for subassembly tail units and fuselage of CN235 type aircraft shipped to Spain. These two components have significantly different assembly times of 566 hours for fuselage and 342 for tail units. Where the two are not completed soon so it is sent in a separate time and causes expensive shipping costs. In addition, the existing assembly time of the two does not correspond to the existing takt time so the completion is often late. Therefore, research will be conducted to determine the appropriate reassignment to answer the problem. The method used is linear programming to find the optimal solution desired with existing conditions. Solutions are searched with the help of CPLEX Studio IDE 12.10.0 software. However, the running result did not produce a solution, so several alternative scenarios were developed and obtained one of the scenarios that reached the desired takt time, namely the completion of the second assembly subassembly within a span of 320 hours. These results are achieved by adding shift work, multiple workers, as well as overlapping the next subassembly work.